2022
DOI: 10.22363/2313-1683-2022-19-4-717-743
|View full text |Cite
|
Sign up to set email alerts
|

Self-regulation and Tolerance for Uncertainty as Resources for the Subjective Well-being of Modern Youth: A Cross-cultural Aspect

Abstract: The study of the socio-cultural specifics of subjective well-being, its determinants and resources are an important task of modern psychology. The authors present the results of an empirical study, the purpose of which is to identify the features of the relationship between conscious self-regulation and tolerance for uncertainty and subjective well-being in young people of different ethnic groups. The study involved 1435 respondents aged 18-35 from five regions of Russia (Karachay-Cherkess Republic, Kabardino-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…At the first stage, a cluster analysis using the k-means method was carried out in order to identify groups of students who differ in the expressiveness of levels of subjective wellbeing, conscious self-regulation and uncertainty tolerance. The basis for the inclusion of these parameters in the division of groups was the data that self-regulation is a significant mechanism for maintaining subjective well-being, including being a mediator of the relationship between well-being and uncertainty tolerance [58]. As a result of clustering of a mixed sample of 1,435 respondents, 7 groups were generated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the first stage, a cluster analysis using the k-means method was carried out in order to identify groups of students who differ in the expressiveness of levels of subjective wellbeing, conscious self-regulation and uncertainty tolerance. The basis for the inclusion of these parameters in the division of groups was the data that self-regulation is a significant mechanism for maintaining subjective well-being, including being a mediator of the relationship between well-being and uncertainty tolerance [58]. As a result of clustering of a mixed sample of 1,435 respondents, 7 groups were generated.…”
Section: Resultsmentioning
confidence: 99%
“…In the crisis of socio-political, economic, and environmental conditions, the issues of finding human resources to successfully cope with new challenges in the changing conditions of life are significantly turning to the problem of resources for assuring the well-being of students: regulatory and personal resources [32], coping behavior [33,34], happiness [35], resilience [36]. It was found that significant factors affecting the stability of subjective well-being are the regulatory abilities of the subject [16], their attitudes to the perception of situations of uncertainty [37], stress resistance [38], intellectual potential [39], self-regulation's reliability [40], social support [41] and basic psychological needs satisfaction [42].…”
Section: The Construct Of "Subjective Well-being"mentioning
confidence: 99%
See 1 more Smart Citation
“…Preschool children are actively developing their executive functions (EF) (Blair & Raven, 2015;Garon et al, 2008). EF development in the preschool period predicts successful adjustment to school and schooling, as well as life achievements, health, well-being, and quality of life in adulthood (Banshchikova et al, 2023;Robson et al, 2020;Scionti et al, 2020;Stichter et al, 2016;Vets, 2023). EF development at preschool age is in uenced by the social situation of a child's development (Vygotsky, 1984), and the children's usage of digital devices is a part of that context (Kurilenko et al, 2022;Soldatova, 2018).…”
Section: Introductionmentioning
confidence: 99%